Comparison Of The Effectiveness Of Massage And Warm Compress On Labor Pain In The Active Phase of The First Stage At The Atikah Midwife Clinic, Sipolu – Polu - Damayanti, Sofi (Cattleya Darmaya Fortuna, 2025)
The Effleurage technique is a massage method that is quite effective in helping reduce back pain in the active phase of labor. Warm compresses reduce muscle spasms and pain intensity in the first stage of labor. The purpose of this study was to compare the effectiveness of massage and warm compresses on labor pain in the active phase of labor at the Atikah Midwife Clinic in 2024. The design of this study was a quasi-experimental time series group comparison design. The population in this study were all 45 mothers giving birth at the Atikah Midwife Clinic in September 2024. The sample was selected using an accidental sampling technique with 30 research subjects divided into 2 intervention groups. The data collection technique was by conducting experiments on mothers in the active phase of labor in the first stage. Data analysis used was the Independent t-test using the SPSS For MS Windows Version 17.0 program. The results of the study found that the average pain intensity value of respondents given massage = 8.20 and the average pain intensity value of respondents given warm compresses = 7.47. The results of the Independent t-test show that the P/Sig (2-tailed) value is 0.000<0.05, which means that the value (p<0.05), then Ho is rejected, while the calculation results show that the t-test is 4.291 while the t-table value df=26.736 and the significance level is 0.05, therefore the calculated t² value>t² table or 4.291>1.706 then Ho is rejected. It is concluded that there is a comparison of the effectiveness of massage and warm compresses in reducing pain intensity in the active phase of labor stage 1. It is recommended that further research be conducted with homogeneous respondents.